Carbon Electrocatalysts For Hydrazine Oxidation: Self-Templating Design Of Hierarchical Porosity Using Barium Carbonate Nanoparticles. Issue 6 (6th April 2020) - Farber, Eliyahu M.; Ojha, Kasinath; Burshtein, Tomer Y.; Eisenberg, David
Abstract : To enable hydrazine as a clean fuel in next-generation fuel cells, electrocatalysts are sought for the hydrazine oxidation reaction (HzOR). Nanostructure of the electrocatalyst plays a crucial role in electrocatalytic activity, yet rational design of surface area, hierarchical porosity, doping and conductivity is highly challenging. We now report a systematic investigation into the structural evolution of excellent HzOR electrocatalysts. This hierarchically porous, N-doped carbon was derived by the tunable self-templating strategy from a simple, well-defined metal-organic coordination polymer (barium nitrilotriacetate). To understand the evolution of structure and its effect on electrocatalytic activity, we combined XRD, HRSEM, TEM, XPS, Raman spectroscopy, elemental analysis, N2 porosimetry, and voltammetry. The sizes, shapes and distributions of BaCO3 nanoparticles and agglomerates were found to be temperature-dependent, and strongly correlated to the hierarchical porosity in the ultimate carbons. The final carbons display a multi-modal porosity, high surface areas (up to 1030 m 2 g −1 ), high nitrogen content (up to 2.7 at%), and excellent graphitization. The best catalysts, prepared at 700 °C and 800 °C, begin electro-oxidizing hydrazine at onset potentials as low as 0.34 V vs RHE at pH 14—within a few 10 s mVs of the best metal-free HzOR electrocatalysts ever reported.